(untitled) (ModaPalavra e-periódico, 2018)
This study proposes situating the process of image construction in the Brazilian soap opera within the scope of Design, based on an epistemological discussion. The research aims to investigate the different approaches related to the formatting ofa possible Theory of Design. Its explanation as science and knowledge are based on the concept of different Design theorists. Thearguments presented here are supported under the process of elaboration of the visual concept of Brazilian soap opera and are evaluated as causers in the common essence that integrates this project in the field of Design as contamination in (re) social configuration.